Social Justice and Economic Sustainability: The Mitigation Role of Islamic Economics Against Natural Disasters - Nurafni Sofya; Indri Perdana; Mita Mita; Afri Tia Deftiana; Iiz Izmuddin (Proceeding of The International Conference on Business and Economics, 2024)
This article discusses the role of Islamic economic mitigation in achieving social justice and economic sustainability in the context of natural disasters. The main focus of this research is how the principles and instruments of Islamic economics, such as zakat, infaq, alms, waqf, andIslamic microfinance institutionscan be used to reduce the social and economic impact of natural disasters. Islamic economics, based on the principles of social justice and redistribution of wealth, offers a holistic and sustainable approach to dealing with disasters. These instruments are capable of providing immediate and effective assistance, as well as supporting long-term rehabilitation and development programs. This research uses a descriptive analysis method with a library research approach. The research results show that Islamic economics not only functions as an economic system, but also as a mechanism for achieving social justice and economic sustainability, which can significantly increase society's resilience to future disasters. This paper emphasizes that the application of Islamic economic principles can be an effective and sustainable solution in dealing with the macroeconomic impacts of natural disasters.